PENGARUH MATA KULIAH PENDIDIKAN PANCASILA TERHADAP KARAKTER NASIONALISME MAHASISWA UNIVERSITAS RIAU ANGKATAN 2024 - Syofia, Ayu; Hambali; Supentri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the character of student nationalism which is currently considered to be weakening, which is influenced by various factors, one of which is globalization. Pancasila Education is present in universities, playing an important role in building student character that has strong values ​​and ethics. However, its influence on student nationalism is not yet clearly known. This study aims to determine the effect of the Pancasila Education course on the character of nationalism of Riau University students class of 2024. This study uses a quantitative method with a statistical approach. The sample amounted to 98 students selected using the Slovin formula. The data analysis technique uses a simple linear regression test with the help of the SPSS version 25 program. The results of the study show that the Pancasila Education course has a positive and significant effect on the character of student nationalism, this is indicated by the F count value (37.875) ≥ F table (3.94). The results of the calculation of the coefficient of determination (R square) test obtained 28.3%, which means that there is an influence of the Pancasila Education course on the nationalistic character of Riau University students in the class of 2024, while 71.7% is influenced by other variables not examined in this study.